Enhancing Wound Healing through Family Support among Diabetes Mellitus Patients: A Study at Bekasi District Hospital - Nurjanah, Siti; Assyfa, Warika Nur; Sartika, Mila (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Diabetes mellitus encompasses a range of metabolic disorders marked by chronic hyperglycemia due to impaired insulin secretion or resistance. One of its serious complications is delayed wound healing, particularly in cases involving gangrene, which demands prolonged medical care. Emotional and practical support from family members plays a crucial role in enhancing patients' motivation, emotional well-being, and recovery outcomes. Objective: This study aimed to evaluate the influence of family support on the effectiveness of wound care in patients with diabetes mellitus. Methods: A quantitative, quasi-experimental study was conducted using a one-group pretest-posttest design. The research involved 30 diabetic patients suffering from gangrenous wounds, selected through total sampling. Data were analyzed using univariate and bivariate approaches, with statistical significance tested via the Wilcoxon signed-rank test. Results: The findings demonstrated a statistically significant effect of family support on wound healing outcomes in diabetic patients (p = 0.000, p < 0.05). Discussion: The presence of supportive family members appears to positively influence the recovery process by fostering patient motivation and adherence to treatment protocols. These results highlight the critical role of family involvement in managing chronic wound care. Conclusion: Family support significantly contributes to successful wound healing in diabetic patients, as observed in Bekasi Regency Hospital.